(untitled) (MATEMATIKA, 2014)
In this paper, we prove common ﬁxed point theorems for four weakly com- patible mappings in chainable fuzzy metric space without taking under consideration the continuity of any mappings. The given results extend and generalize several known results of ﬁxed point theory in diﬀerent spaces. The present study point out that the continuity of any mapping is not required for existence of ﬁxed point in a complete chainable fuzzy metric space. Keywords : Common Fixed Point; e`-Chainable Fuzzy metric space; Weakly Compatible Mappings 2010 Mathematics Subject Classiﬁcation 47H10l; 54H25.